STUDENTS’ PERCEPTION OF STORYTELLING TECHNIQUE IN ENHANCED SPEAKING SKILL - Muh. Soghirun; Fatimah Hidayahni Amin; Sukardi Weda (Universitas Negeri Makassar, 2022)
The objective of this research was to find out and describe student perception of the implementation of storytelling enhancing their speaking skills the third-grade students at Sekolah Usaha Perikanan Menengah (SUPM) Bone. The researchers applied the descriptive method. The data was collected by questionnaire. In analyzing data, the researchers used the Likert scale which includes five-point scales: strongly agree, agree, undecided, disagree, and strongly disagree. The population of this research was 162 students in the third grade in the academic year of 2021/2022. The sample took by using the cluster random sampling technique. The results confirmed that the mean score of the student perception of the use of storytelling in improving students speaking is 40.35 which is categorized as strongly fine. The analysis of the student perception showed that the implementation of the storytelling method in the English learning method affected significantly student perception of attending the class during teaching English speaking.